2008 Solid-State, Actuators, and Microsystems Workshop Technical Digest 2008
DOI: 10.31438/trf.hh2008.3
|View full text |Cite
|
Sign up to set email alerts
|

Flip-Chip Integrated Soi-Cmos-Mems Fabrication Technology

Abstract: A fully-dry, flip-chip fabrication technology was developed for the integration of high fill factor, silicon-on-insulator (SOI) structures and CMOS-MEMS actuators. An SOI mirror array with a fill factor of 95% and radius of curvature >1.3 m was fabricated on CMOS-MEMS electrothermal actuators using this technology. The unloaded actuators achieved an optical scan range of >92º. Following flip-chip bonding with high temperature epoxy, the structures were released using deep reactive ion etching (DRIE). Aspect ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…McManamon et al in 1993 [12], he published an all-thing-considered review paper to summarize its nearly 30 years of development [13] including liquid crystal polarization gratings to achieve 99.5% diffraction efficiency [14], simulation on high efficiency improvement [15], volume holographic to amplify steering angle [16], and the scattering free polymer network liquid crystal invented by Dr. Sun et al to overcome the transparency reduction on the submillisecond liquid crystal devices [17,18]. Meanwhile, the concept of LC-OPA has been suggested into the midinfrared domain [19] and even some alternative methods for steering laser beam such as lenslet array [20] and MEMS-based [21].…”
Section: Introductionmentioning
confidence: 99%
“…McManamon et al in 1993 [12], he published an all-thing-considered review paper to summarize its nearly 30 years of development [13] including liquid crystal polarization gratings to achieve 99.5% diffraction efficiency [14], simulation on high efficiency improvement [15], volume holographic to amplify steering angle [16], and the scattering free polymer network liquid crystal invented by Dr. Sun et al to overcome the transparency reduction on the submillisecond liquid crystal devices [17,18]. Meanwhile, the concept of LC-OPA has been suggested into the midinfrared domain [19] and even some alternative methods for steering laser beam such as lenslet array [20] and MEMS-based [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, this method results in larger than 8 µm variation over a 1 mm distance on the backside Si profile, which leads to variations in the masses and springs. Other previous work has demonstrated a mirror [3] using Si DRIE and ARDE to form a 100 µm-thick bulk Si mass with approximately 5µm thickness variation. Process variations such as thickness variation and beam width variation cause changes of the masses, spring constants, and consequently resonant frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…-(3). Using the NODAS model, the gradient parameters inside the variation matrix J in(2)are determined and chosen based on the sensitivity of the displacement of mass m 1 with respect to Δt o , Δt x and Δw.…”
mentioning
confidence: 99%
“…Wu et al demonstrated a 4 × 4 electrothermal bimorph-based TTP MMA [15], in which each subaperture is 0.5 mm × 0.5 mm in size and can achieve ±30 • optical deflection and a maximum 215-μm piston stroke, all at less than 5 V. The fill factor of this device in the MMA region is 31%. Gilgunn et al presented a 3 × 3 silicon-oninsulator-complementary metal-oxide-semiconductor-MEMS (SOI-CMOS-MEMS) electrothermal MMA with bimorph actuators [16]. The device achieved an area fill factor of 95%, with each element size of 1.0 mm × 1.0 mm.…”
mentioning
confidence: 98%
“…More importantly, to integrate the SCS mirror plate with the comb-drive actuators or electrodes, one or more dedicated bonding steps or trench-filling and chemical-mechanicalpolishing (CMP) steps are required, which make the fabrication complicated, costly, and low yield [11]- [13]. Electrothermally actuated TTP MMAs have also been reported, based on either thermal bimorph actuators [15], [16] or thermal-pneumatic actuators [17]. Thermal-pneumatic actuation usually has slow response and high power consumption.…”
mentioning
confidence: 99%